Job quality of the PhD graduates in Portugal - Cordeiro, Pedro Alexandre de Oliveira (2019)
Job quality has been a subject of growing interest by the international institutions and academics in the last two decades. Economic crisis and increasing supply of graduates renewed the debate about the benefits of investments in higher education and the working conditions of young highly skilled people. This dissertation draws on European Union Labour Force Survey data from the year 2014 and examines the job quality of the PhDs holders in Portugal. It should be noted that literature on PhD graduates jobs is scarce, so this research attempts to fill this gap in the literature. The jobs were examined through a fuzzy clustering analysis, which enabled us to identify typologies of PhDs jobs. The empirical results pointed to three fuzzy clusters and show that one type of job comprises foreign young women with precarious and part-time jobs, who are overqualified and unsatisfied since are looking for another job. Another cluster aggregates senior PhD holders with high-wages, stability and good work-life balance. Finally, the third typology differs from the latter since PhD graduates seem to find it difficult to balance personal life and professional responsibilities. The findings corroborate previous research in that young people are facing increasing difficulties in the labour market; this affects also highly skilled young people.